Evolutionary Based Set Covers Algorithm with Local Refinement for Power Aware Wireless Sensor Networks Design - Abbas, Mustafa N.; Attea, Bara'a A.; Kadhim, Nasreen J. (Iraqi Journal of Science, 2018)
Establishing coverage of the target sensing field and extending the network’s lifetime, together known as Coverage-lifetime is the key issue in wireless sensor networks (WSNs). Recent studies realize the important role of nature-inspired algorithms in handling coverage-lifetime problem with different optimization aspects. One of the main formulations is to define coverage-lifetime problem as a disjoint set covers problem. In this paper, we propose an evolutionary algorithm for solving coverage-lifetime problem as a disjoint set covers function. The main interest in this paper is to reflect both models of sensing: Boolean and probabilistic. Moreover, a heuristic operator is proposed as a local refinement operator to improve the quality of the solutions provided by the evolutionary algorithm. Simulation results show the necessity to inject a heuristic operator within the mechanism of evolutionary algorithm to improve its performance. Additionally, the results show performance difference while adopting the two types of sensing models.